Mixed Picture of Readiness for Adoption of Evidence‐Based Prevention Programs in Communities: Exploratory Surveys of State Program Delivery Systems. Issue 3 (20th March 2015) - Spoth, Richard; Schainker, Lisa M.; Redmond, Cleve; Ralston, Ekaterina; Yeh, Hsiu-Chen; Perkins, Daniel F.
Abstract: An emerging literature highlights the potential for broader dissemination of evidence‐based prevention programs in communities through existing state systems, such as the land grant university Extension outreach system and departments of public education and health (DOE–DPH). This exploratory study entailed surveying representatives of the national Extension system and DOE–DPH, to evaluate dissemination readiness factors, as part of a larger project on an evidence‐based program delivery model called PROSPER. In addition to assessing systems' readiness factors, differences among US regions and comparative levels of readiness between state systems were evaluated. The Extension web‐based survey sample N was 958 and the DOE–DPH telephone survey N was 338, with response rates of 23 and 79 %, respectively. Extension survey results suggested only a moderate level of overall readiness nationally, with relatively higher perceived need for collaborative efforts and relatively lower perceived resource availability. There were significant regional differences on all factors, generally favoring the Northeast. Results from DOE–DPH surveys showed significantly higher levels for all readiness factors, compared with Extension systems. Overall, the findings present a mixed picture. Although there were clear challenges related to measuring readiness in complex systems, addressing currently limited dissemination resources, and devising strategies for optimizing readiness, all systems showed some readiness‐related strengths.